Strategic Integration to R&D Projects: a case study of a French multinational in the energy sector (Research, Society and Development, 2022)
The company that seeks competitiveness in the market in which it operates and in future markets has its strategic technologies as one of the factors of competitiveness. However, in order to have the expected effect, it is important that the projects developed by R&D adhere to the company's strategic planning in order to maximize results. The objective of this article is to evaluate the adherence between the projects developed in R&D and the strategic planning. In this study, the research carried out has an exploratory qualitative nature and the data were collected through semi-structured interviews and questionnaires. As a result of the research, the weaknesses and strengths of the company were pointed out according to the employees' affirmation in relation to the adherence of R&D projects and strategic planning. Participants also agreed on the importance of aligning the company's strategy and R&D.